Finding a New Crystalline Sponge from a Crystallographic Database. Issue 2 (15th December 2016) - Inokuma, Yasuhide; Matsumura, Kazuki; Yoshioka, Shota; Fujita, Makoto
Abstract: Empirical searching conditions were adopted to identify suitable candidates from the Cambridge Structural Database (CSD) for crystalline sponge hosts for X‐ray crystallographic analysis of incoming guest compounds. After optimization of the solvent and soaking conditions, one of the candidates was used as a crystalline sponge for the structure determination of an aromatic guest. Abstract : Seek, and you will find : Promising candidates for new crystalline sponges for analysis of the structures of non‐crystalline compounds by X‐ray diffraction were selected from a crystallographic database using semi‐empirical searching conditions. After optimization of the guest‐soaking conditions, a new crystalline sponge with large one‐dimensional channels was discovered.